Identification of The Geothermal Heat at Mount Iyang-Argopuro Based on a Data Image of Landsat 8 Satellite and a Data Gravity of GGMPlus Satellite - Bahtiar, Ega Abi; Suprianto, Agus; Supriyadi, S. (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2021)
In Indonesia is the Iyang-Argopuro Volcano Complex. The Research uses remote sensing methods and gravity methods conducted to study thermal anomalies and subsurface structures using Data images of Landsat 8 satellite and a data gravity of GGMPlus satellite. Moreover, the study aims to estimate the number of hoisting manifestations of the earth's heat at the compound of the Iyang-Argopuro volcano. Landsat 8 satellite image data is a spectral band (band 1-9) and a thermal band (band 10 and 11). The data was done in radiometric corrections, radiance correction, and reflex corrections, and was thus obtained a value of ground surface temperature (LST). The data was done in radiometric corrections, radiance correction, and reflectance corrections, to get an LST value. Processing data gravity of GGMPlus satellites with a bouguer correction, terrain corrections up to get a Complete Bouguer Anomaly (ABL) value. Furthermore, the ABL value consisting of regional and local anomalies is separated using an upward continuation filter to obtain local anomaly values. The results obtained from this study are five points of geothermal manifestation locations in the Iyang-Argopuro Volcano Complex which are located in the northern, central, southern and eastern parts. Manifestations in the northern, central, and northeastern parts have ground surface temperatures of 24-31 ̊C. While manifestations in the central and eastern parts have a surface temperature of land 21-31 ̊C. The high ground temperature values at the five locations were associated with low gravity values ranging from -20 mGal to -10 mGal. The low gravity value is assumed to have a rock structure with a low-density value. Low-density rock structures have the possibility of an outflow zone causing the soil surface temperature to be relatively high.